Regiodivergent Asymmetric Conjugate Addition of 2-Furfuryl Ketones to Nitroalkenes Using Thiourea Organocatalysts - Koda, Taro; Akutsu, Hiroshi; Suzuki, Mitsuaki; Nakashima, Kosuke; Hirashima, Shin-ichi; Yoshida, Akihiro; Miura, Tsuyoshi; Yamanoi, Takashi (Synlett, 2025)
We recently reported the asymmetric ε-regioselective conjugate addition of 2-furfuryl ketones to nitroalkenes utilizing a thiourea–pyrrolidine organocatalyst, resulting in good yields and enantioselectivities. In this study, we present a novel approach for the asymmetric α-regioselective conjugate addition of 2-furfuryl ketones to nitroalkenes using a thiourea–tertiary amine organocatalyst, which has not been previously documented. The reactions produced α-regioselective addition products in high yields and with excellent stereoselectivities. Thus, this work marks the first example of regiodivergent asymmetric conjugate addition of 2-furfuryl ketones to nitroalkenes.
Keywords: Organocatalyst; Asymmetric; Conjugate addition; Regiodivergent reaction; 2-Furfuryl ketones; Nitroalkene